Molecular characterization of infectious myonecrosis virus (IMNV) isolated from the shrimp Litopenaeus vannamei farmed in Ceará State, Brazil - Coelho-Melo,Maria Verônyca (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2014)
The shrimp Litopenaeus vannamei, one of the most important species in world aquaculture, has seriously affected by infectious myonecrosis virus (IMNV) that causes up to 70% mortalities. With the aim of improving the development of new strategies for rapid and reliable diagnosis, we isolated IMNV, from L. vannamei farmed in Brazil, through a discontinuous sucrose gradient, and sequenced cDNA fragment encoding the major capsid protein from this virus. Nucleotides sequences corresponding to the viral capsid protein was obtained by RT-PCR and confirmed by automatic sequencing. Comparison with sequences which encode the capsid protein obtained from Indonesia isolates showed a high identity.